Building Confidence, Diminishing Stress: A Clinical Incivility Management Initiative for Nursing Students - Younglee Kim; Yeon Sook Kim; Henrietta Nwamu; Anne Lama (MDPI AG, 2024)
Objective: The aim of this study was to evaluate the effectiveness of an interactive program designed to reduce nursing students' perceived stress and improve self-efficacy and readiness to professionally address incivility during clinical practice. Background: Incivility in clinical settings adversely impacts learners, educators, institutions, and healthcare systems, undermining safety and the teaching-learning process. Despite its increasing global prevalence, effective interventions remain largely unexplored. Methods: Our mixed-methods study, conducted from March to April 2024, involved senior baccalaureate pre-licensure nursing students (N = 35) from a California State University. The three-week, one-hour-per-week, interactive clinical incivility management program was developed through an extensive literature review. Pre- and post-intervention differences were assessed using a 10 min self-administered online survey that included the Uncivil Behavior in Clinical Nursing Education (UBCNE; 12 items), Perceived Stress Scale (PSS; 10 items), General Self-Efficacy Scale (GSE; 10 items), and a sample characteristics questionnaire (11 items). A one-hour face-to-face focus group (n = 11) then provided qualitative data on personal experiences of clinical incivility. Quantitative data were analyzed using SPSS version 27, while qualitative data were analyzed using Colaizzi's method. Results: Clinical incivility prevalence was 71.4% (n = 25 out of 35). No statistically significant differences were found in UBCNE, PSS, and GSE scores between pre- and post-intervention. However, professional responses to clinical incivility significantly improved after the intervention (t = −12.907, p < 0.001). Four themes emerged from the qualitative data: (a) uncivil behaviors or language from nurses, (b) emotional discouragement and low self-confidence, (c) resource and personnel shortages at clinical sites for education, and (d) the necessity for interventions to manage clinical incivility. Conclusions: Nursing schools and clinical agencies should collaborate to establish monitoring systems, enhance communication, and implement evidence-based policies and interactive interventions to prevent and manage clinical incivility experienced by nursing students from clinical sites.